2012
DOI: 10.1016/j.jcma.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of erosive esophagitis in Taiwan

Abstract: The current prevalence of erosive esophagitis in Taiwan is 17.3%. Male sex, smoking, obesity, and hiatus hernia are four independent risk factors for the development of erosive esophagitis in the Taiwanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Recent data have shown that long-term use of LES relaxing medications, such as theophylline, is associated with EAC [55]. However, the epidemiological studies investigating the effects of tea on GERD are scant and the results are conflicting [6,15,29,5661], possibly because of difficulty in assessing the quantity and the quality of tea in a population-based study. Many culturally-related drinking habits, such as the consumption of black tea, green tea and strong tea [56], along with drinking tea at hot temperatures [62], and adding nutrients such as cream or sugar [49], may contribute differently to the reflux or irritation of esophageal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that long-term use of LES relaxing medications, such as theophylline, is associated with EAC [55]. However, the epidemiological studies investigating the effects of tea on GERD are scant and the results are conflicting [6,15,29,5661], possibly because of difficulty in assessing the quantity and the quality of tea in a population-based study. Many culturally-related drinking habits, such as the consumption of black tea, green tea and strong tea [56], along with drinking tea at hot temperatures [62], and adding nutrients such as cream or sugar [49], may contribute differently to the reflux or irritation of esophageal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy-diagnosed erosive esophagitis has been increasing in Asia over 2 decades, with a reported prevalence of 3.3 to 8.5% in Korea, China and Japan except Taiwan (ranging from 17.3 to 18.3%) which is similar to other Western developed countries 1-6. The reasons for the high prevalence rate of erosive esophagitis are not clearly demonstrated, however, it could be related with western diet, increased obesity and aging of population 6.…”
Section: Introductionmentioning
confidence: 90%
“…The reasons for the high prevalence rate of erosive esophagitis are not clearly demonstrated, however, it could be related with western diet, increased obesity and aging of population 6. The prevalence rate of erosive esophagitis was 8%, in prospective nationwide multicentre studies of 25,536 health check-up Koreans 7.…”
Section: Introductionmentioning
confidence: 99%
“…4 Regarding the risk factors leading to GERD, the authors also indicated that male gender, smoking, increased body mass index, and hiatal hernia were independent risk factors among the enrolled subjects. 7 However, these reported GERD risk factors are not new in Taiwan because the literature already indicates that male gender, 2,8,12 old age, 12 hiatal hernia, 2,8 smoking, 5,9,12 alcohol consumption, 9,12 metabolic syndrome, 9,12 high fasting blood glucose level, 12 high blood pressure, 12 obesity, 2,5,12 and chronic obstructive pulmonary disease 8 are well-known confounding factors that can lead to GERD, including EE. The authors are just confirming the known GERD risk factors again.…”
mentioning
confidence: 99%